Strengthening Bonds of Friendship Between Sino-Pakistan through Chinese Author’s Translated Work Published in Pakistan’s National Language (Urdu) - Muhammad Asif; Muhammad Usman; Majid Ali; Abdoulaye M’Begniga; Liu Yang (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The demonstration and leading role of the China-Pakistan Economic Corridor are axiomatic, and the political, economic, and cultural exchanges between China and Pakistan have been further strengthened. The two sides' positions in each other’s diplomatic strategy have become more prominent, and the relationship between Pakistan and China has become a model for state-to-state relations in the world. The cooperation between the two countries in the China-Pakistan economic corridor has also become a model for global cooperation for the benefit of the people. A society's ability to disseminate and diffuse information would be severely limited without publishing books. Knowledge transmission is an integral aspect of it. There is a strong need to introduce mainstream thinkers' works, increase publication investment, cultivate professional editors, enrich publication types, and expand cultural exchange styles. The study explores Chinese books translation work published in Pakistan National Language in Urdu. This article focuses on the translator's role as a cultural mediator who must faithfully communicate the intricacies of the literary material. The debate's heart is translating culturally unique things like proverbs, figurative language, references to religion, mythology, literature, and stylistics. Literary publishing on the web represents a new, era of creative expression and enhanced democratization of literary culture, and its impact on writers, readers, publishers, and libraries has been significant. The study revealed that In sufficiencies such as lack of introduction, the low conversion rate of published works, and unstable publishing structure. We believe that it is necessary to encourage to publish cultural exchanges and strengthen the relationship between both countries.